Bursa of Fabricius–independent B cells establish an IgA-mediated intestinal barrier that safeguards gut–liver homeostasis - Ryota Hirakawa; Motoshi Hisamatsu; Sayoko Maekawa; Eiki Asai; Miyuko Ohta; Ayumi Matsuo; Kunihiro Okano; Toh Miyazaki; Motofusa Akiyama; Masaaki Toyomizu; Jahidul Islam; Mutsumi Furukawa; et al. (Proceedings of the National Academy of Sciences, 2026)
The bursa of Fabricius (BF), a specialized lymphoid structure in birds, regulates avian B-cell development. However, the BF starts to regress posthatching, suggesting that as-yet-unidentified structures assume this function during maturation. This study reveals that BF-independent B-cell genesis involving the gut cecal tonsils (CTs) predominates over the BF-dependent pathway posthatching. Although B-cell progenitors originating from the bone marrow (BM) typically migrate to the BF, we identified a population that instead migrates to the CTs through CXCL12/CXCR4-mediated chemotaxis. These BF-independent CXCR4 + pre-B cells acquired surface IgM expression within the CT follicular region (FR) and differentiated into immunoglobulin A (IgA)-producing plasma cells. Inhibition of CXCR4 + cell influx from the BM impaired formation of the FR, altered the responsiveness of intestinal IgA to commensal bacteria, promoted gut dysbiosis, allowed translocation of pathogenic bacteria (e.g., Streptococcus alactolyticus ) to the liver, and ultimately caused hepatic inflammation and metabolic dysfunction. These abnormalities were reversed by administering an IgA-enriched fecal preparation derived from healthy chickens. Collectively, these results reveal the existence of a population of BF-independent B cells that function in CTs. These cells represent a promising target for maintaining and improving the immunological and microbiological environment of the avian intestinal tract, which is closely linked to hepatic homeostasis.